Empowering Young Girls in Pakistan through HPV Vaccination and Cervical Cancer Awareness: HPV Vaccination and Cervical Cancer Awareness - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2025)
Cervical cancer is a major public health challenge in Pakistan, with over 5,000 new cases and nearly 3,000 deaths each year, making it the third most common cancer among women and the second most frequent among those aged 15 to 44.(1, 2) The disease is often diagnosed late, contributing to disproportionately high mortality compared to neighboring countries. Human papillomavirus (HPV) infection is the primary cause, with high-risk genotypes 16 and 18 responsible for nearly 90% of invasive cervical cancers, and recent data from Karachi show a prevalence of 16.7% among tested women.(3, 4) Despite being largely preventable through vaccination and early detection, cervical cancer in Pakistan remains neglected due to extremely low awareness, harmful misconceptions, lack of organized screening, and deep-rooted cultural stigma surrounding sexual and reproductive health. Many people wrongly believe that cervical cancer only affects women who are sexually active or have multiple partners, creating stigma that discourages open discussion and preventive care.(5) These cultural taboos and widespread opposition to addressing sexual and reproductive health leave countless women without access to life-saving knowledge and early detection. The silence and shame surrounding cervical cancer have allowed it to remain hidden, leaving Pakistani women disproportionately vulnerable to a disease that could otherwise be prevented or treated in time.(6, 7) In September 2025, Pakistan took a historic step by launching its first nationwide Human Papillomavirus (HPV) vaccination campaign, targeting 13 million girls aged 9 to 14 years. The vaccine is being provided free of charge through schools, health facilities, outreach sites, and mobile teams, with support from WHO, UNICEF, and Gavi. This initiative will not only protect young girls from cervical cancer a disease that claims thousands of lives each year, but also integrate HPV vaccination into routine immunization, ensuring protection for future generations.(8) This campaign is more than just a health intervention; it is an empowerment movement for women and girls. By protecting them early, we are giving them the right to a healthier future, free from a preventable disease. Families, teachers, and communities must come together to encourage every eligible girl to get vaccinated. With collective effort, Pakistan can break the silence around women’s health, eliminate cervical cancer, and empower women to lead stronger, healthier lives. The way forward is clear to make screening services accessible, spread accurate information to every household, and create safe spaces where women can seek care without fear or stigma.